The Correlation of Academic Conscience and Students' Academic Performance with the Mediating Role of Academic Hardiness - Fardin Seifi; Masoud Hejazi; Afsaneh Sobhi; Qamar Kiani (Shiraz University of Medical Sciences, 2022)
Background: Academic performance, as a behavioral consequence, is of great importance for students and is considered as significant indicator for evaluating educational systems and identifying the factors affecting them. This led us to study the relationship of academic consciences and academic performance with the mediating role of academic hardiness in ninth grade students in Zanjan. Methods: As the statistical population, we selected all the ninth-grade male students of district 1 of education department of Zanjan, Iran in 2018-2019. The present research was conducted as a descriptive correlational study. The statistical sample comprised 295 of these students. Data were collected using McIlroy and Banting Academic Conscience Questionnaire and Academic Hardiness Questionnaire of Benishkak and colleagues. Additionally, total academic grade point average (GPA) of the students was utilized to assess academic performance. The data were analyzed by Pearson correlation and stepwise regression tests. To determine the mediating role of academic hardiness, Baron and Kenny method was also used. Results: The correlation of the variable of academic conscience with the academic performance equaled r=0.255, P=0.042, effort control equaled r=0.131, P=0.047, emotion control equaled r=0.181, P=0.045, challenge ability was r=0.161, P=0.045, and hardiness was r=0.195, P=0.044; these results were statistically significant. This study also revealed that in the relationship between academic conscience and academic performance, academic hardiness has a mediating role. Conclusion: Academic conscience, by affecting academic hardiness, can contribute to students' academic performance.